Preparation method of renewable magnetic porous carbon adsorption material

Magnetic porous carbon materials are prepared through heat treatment and loading processes of biomass carbon sources, which solves the problems of high costs and environmental pollution in the preparation of existing porous carbon materials, and realizes efficient and environmentally friendly preparation and rapid recovery of magnetic porous carbon materials. It is suitable for Adsorption treatment of heavy metal ions.

CN119258986AActive Publication Date: 2025-01-07SINOSTEEL MAANSHAN INST OF MINING RES CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411596299.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-07
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

There are problems such as high cost, environmental pollution, and difficulty in separation and recycling after adsorption during the preparation of existing porous carbon materials. The porous carbon materials prepared by biomass carbon sources lack magnetic properties, which limits their application.

Method used

Using biomass carbon source as raw material, magnetic porous carbon materials are prepared through specific heat treatment and loading processes, including the preparation of biocarbons, the loading of magnetic substances and the activation of porous carbons, and the magnetic substance FeCl3 reacts with NaAc at high temperature to form. Fe3O4 is then activated in a carbon dioxide atmosphere to form a magnetic porous carbon adsorption material with excellent properties.

Benefits of technology

It realizes the preparation of low-cost and environmentally friendly magnetic porous carbon materials, with high specific surface area and excellent adsorption performance, is suitable for the adsorption treatment of a variety of heavy metal ions, and achieves rapid recycling and regeneration through magnetic separation technology, reducing the cost of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126989590000071
    Figure BDA0005126989590000071
  • Figure BDA0005126989590000082
    Figure BDA0005126989590000082
Patent Text Reader

Abstract

The invention discloses a preparation method of a renewable magnetic porous carbon adsorption material. The preparation method comprises the following steps: crushing and drying a biomass carbon source serving as a raw material to obtain biomass carbon powder; the preparation method comprises the following steps: dissolving FeCl3. 6H2O in ethylene glycol, adding NaAc, transferring into a polytetrafluoroethylene reaction kettle, adding biomass carbon powder, carrying out high-temperature reaction, separation, cleaning and drying, carrying out heat treatment in a protective atmosphere to form a biomass carbonized material, and carrying out ball milling and activation on the biomass carbonized material to obtain the magnetic porous carbon adsorption material which can effectively remove pollutants. The method is low in cost and environment-friendly, and the prepared magnetic porous carbon material has a reasonable aperture structure, a high specific surface area and excellent magnetic performance and is suitable for adsorption treatment of various pollutants. The biomass carbon source is adopted as the raw material, the cost is low, regeneration is achieved, a large number of chemicals are not needed in the whole preparation process, wastewater discharge is reduced, and the green chemistry concept is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of porous carbon adsorption materials for environmental protection, and in particular relates to a preparation method of a magnetic porous carbon adsorption material. Background Art

[0002] With the rapid development of industrialization and urbanization, pollutants such as heavy metals have posed a serious threat to the environment and human health. Heavy metal pollutants are not only difficult to degrade, but can also accumulate in organisms, leading to various health problems. Although traditional adsorbents, such as activated carbon and resins, can remove these pollutants to a certain extent, they have problems such as limited adsorption capacity, difficulty in regeneration, and high cost. Therefore, the development of an efficient, renewable and low-cost adsorbent material is of great significance to environmental protection and human health.

[0003] Porous carbon materials have attracted extensive attention due to their high specific surface area, excellent adsorption performance and good chemical stability. However, the traditional preparation process of porous carbon materials often requires the use of a large amount of chemicals, which is not only costly but also may cause secondary pollution to the environment. In addition, ordinary porous carbon materials are difficult to effectively separate and recycle after adsorption, which limits their promotion in practical applications.

[0004] In order to overcome these challenges, researchers began to explore the use of biomass carbon sources as raw materials to prepare porous carbon materials. Biomass carbon sources are not only low-cost and renewable, but their preparation process is generally more environmentally friendly. However, most of the porous carbon materials currently prepared using biomass carbon sources do not have magnetism, which to a certain extent limits their application in adsorption treatment. Therefore, giving porous carbon materials magnetism and achieving rapid recovery and regeneration of adsorption materials through magnetic separation technology is of great significance for greatly reducing the cost of use and improving treatment efficiency.

[0005] Chinese patent application 201410128911.2 discloses a method for preparing agricultural biomass carbon-based magnetic adsorption materials. The method uses agricultural biomass derived from plant organisms as raw materials, adopts a loading process of ultrasonic blending of trivalent iron ions and biomass, alkali precipitation and low-temperature hydrothermal carbonization magnetization process to obtain a biocarbon adsorption material with magnetic properties. This method can not only simultaneously realize the preparation and magnetization process of carbon adsorption materials, but also has a wide range of raw materials, is cheap and easy to obtain, but this method requires ultrasonic treatment for 0.5-2h, and long-term exposure to a high noise environment may be detrimental to the health of the experimenters.

[0006] Therefore, the present invention aims to provide a method for synthesizing a porous carbon material with magnetic properties by using a biomass carbon source as a raw material through a specific heat treatment and loading process. The method is not only low-cost and environmentally friendly, but also the prepared magnetic porous carbon material has excellent performance and is suitable for the adsorption treatment of various pollutants. Summary of the invention

[0007] The purpose of the present invention is to address the problems that most porous carbon materials prepared from biomass carbon sources do not have magnetism, the technical difficulties such as the use of large amounts of chemicals and increased production costs in the existing porous carbon adsorption material preparation process, which leads to environmental pollution and difficulty in effective separation and recovery after adsorption, and the hazards of ultrasonic high noise in the preparation process of agricultural biomass carbon-based magnetic adsorption materials, and to provide a method for preparing a renewable magnetic porous carbon adsorption material that is green, environmentally friendly, has excellent magnetic properties, has a pore structure, and has a high specific surface area.

[0008] In order to solve the above problems, the present invention provides a method for preparing a renewable magnetic porous carbon adsorption material, which is implemented by the following process:

[0009] (1) Preparation of biochar: Select biomass carbon source as raw material, crush and dry to obtain biomass carbon powder, and control the particle size of the biomass carbon powder to be in the range of 2-20 μm;

[0010] (2) Loading of magnetic material: taking an appropriate amount of FeCl3·6H2O and completely dissolving it in ethylene glycol, then adding an appropriate amount of NaAc, stirring to obtain a uniform yellow solution, then transferring the yellow solution to a polytetrafluoroethylene reactor, adding the biomass carbon powder in step (1) to the reactor, stirring evenly and heating to 180-280°C for high temperature reaction; after the reaction is completed, cooling to room temperature, centrifugally separating and washing with ethanol and deionized water three times, and then drying in a vacuum drying oven; then heating the dried product in a protective atmosphere step by step to a temperature of 600°C-800°C for heat treatment, so that the biomass carbon is carbonized and a biomass carbonized material with a preliminary pore structure is formed;

[0011] (3) Activation of porous carbon: ball-milling the biomass carbonized material obtained in step (2), and controlling the particle size of the ball-milled product to be in the range of 1-15 μm; activating the ball-milled product in a carbon dioxide atmosphere at a temperature of 800° C.-1000° C. to obtain a magnetic porous carbon adsorption material product.

[0012] Preferably, the method for preparing a renewable magnetic porous carbon adsorption material of the present invention further comprises the following steps:

[0013] S1 parameter test: test the pore structure of the prepared magnetic porous carbon adsorption material, including specific surface area, total pore volume, and average pore diameter;

[0014] S2 Application effect test: The adsorption performance of the prepared magnetic porous carbon material was tested, including adsorption capacity, adsorption rate, selectivity, recovery rate and cycle performance;

[0015] S3 Optimization Control: Based on the test results of S1 and S2, the relevant technical parameters of steps (1), (2), and (3) are optimized and controlled to finally produce a product with a specific surface area of ​​>1250m 2 / g, total pore volume>0.52cm 3 / g of magnetic porous carbon adsorption material product.

[0016] Preferably, in step (1), the drying procedure is drying at 60-100° C. for 18-24 hours; the biomass carbon source includes but is not limited to coconut shells, straws, rice husks, wood, bamboo, bagasse, nut shells, wheat starch, and corn starch; in step (2), the protective atmosphere is nitrogen or argon.

[0017] Preferably, in step (2), the mass ratio of FeCl3·6H2O to NaAc is 1:

[0018] (1.5-4.5), the mass ratio of FeCl3·6H2O to ethylene glycol is 1:(30-40), and the mass ratio of FeCl3·6H2O to biomass carbon source is 1:(1-5); the high temperature reaction time is 8-15h; the vacuum drying condition is drying at 60-100°C for 6-10h; the dried product is heated step by step to 600°C-800°C in a nitrogen protective atmosphere for heat treatment for 1.5-2.5h.

[0019] Preferably, in step (3), the ball milling condition is 200-400 rpm for 1-5 min; the activation temperature is 850° C.-950° C., and the activation time is 8-15 h.

[0020] Preferably, in step (2), the mass ratio of FeCl3·6H2O to NaAc is 1:

[0021] (2.5-3.5), the mass ratio of FeCl3·6H2O to ethylene glycol is 1:(33-39), the mass ratio of FeCl3·6H2O to biomass carbon source is 1:(1-2), the high temperature reaction time is 8-15h, the vacuum drying condition is drying at 60-100°C for 6-10h, and the dried product is heated to 650°C-750°C in a nitrogen protective atmosphere for heat treatment for 1.5-2.5h; in step (3), the ball milling condition is processing at a speed of 200-400rpm for 1-5min, the activation temperature is 850°C-950°C, and the activation time is 8-15h.

[0022] Furthermore, in step (2), the high temperature reaction temperature is 180-230°C, the high temperature reaction time is 9-12h, the vacuum drying condition is 60-100°C for 6-10h, and the heat treatment time is 1.8-2.5h; in step (3), the activation temperature is 890°C-900°C, and the activation time is 11-13h.

[0023] Furthermore, in step (2), the dried product is heated to 150°C at 5°C / min in a nitrogen atmosphere, maintained for 30 min, then heated to 450°C at 1°C / min, maintained for 2 h, and then heated to 700°C at 5°C / min, maintained for 2 h.

[0024] Compared with the prior art, the preparation method of a renewable magnetic porous carbon adsorption material of the present invention has the following beneficial effects:

[0025] (1) Low cost: Biomass carbon source is used as raw material, which is low cost and renewable.

[0026] (2) Environmentally friendly: The entire preparation process does not require the use of large amounts of chemicals, reduces wastewater discharge, and complies with the concept of green chemistry.

[0027] (3) Excellent performance: The prepared renewable magnetic porous carbon material has a reasonable pore structure, high specific surface area and excellent magnetic properties. The specific surface area is generally between 1250-2000m 2 / g range, the total pore volume is generally 0.51-0.83cm 3 / g, with an average pore size of 1.60-1.82nm; the prepared renewable magnetic porous carbon material is suitable for the adsorption treatment of various heavy metal ion pollutants, and is suitable for the adsorption of Cr in sewage. 6+ 、Cd 2+ , Pb 2+ , Cu 2+ It has a good adsorption effect on heavy metal ions such as Cr 6+ The removal rate of Cd 2+ The removal rate of Pb 2+ The removal rate of Cu 2+ The removal rate is as high as over 91%.

[0028] (4) Easy to recycle and regenerate: After loading magnetic substances on porous carbon materials, magnetic separation technology can be used to achieve rapid recovery and regeneration of adsorbent materials, thereby reducing the cost of use. DETAILED DESCRIPTION

[0029] To describe the present invention, the preparation method of a regenerable magnetic porous carbon adsorption material of the present invention is further described in detail below in conjunction with examples. However, the present invention is not limited to the examples.

[0030] Example 1

[0031] Take an appropriate amount of soybean straw and crush it with a crusher, screen it with 5000 mesh, and take the straw under the screen and dry it at 100℃ for 18h. Take 2.6gFeCl3·6H2O and completely dissolve it in 80mL ethylene glycol, then add an appropriate amount of 7.2g NaAc, stir to get a uniform yellow solution, then transfer the solution to a polytetrafluoroethylene reactor with a capacity of 100mL, add 4g of dry straw powder to the reactor, stir evenly and react at 200℃ for 10h. After cooling to room temperature, centrifuge and wash it with ethanol and deionized water three times, and place it in a 60℃ vacuum drying oven to dry for 6h. Then the product is heated to 150℃ at 5℃ / min in a nitrogen atmosphere, kept for 30min, then heated to 450℃ at 1℃ / min, kept for 2h, and then heated to 700℃ at 5℃ / min, kept for 2h, and then cooled to room temperature naturally. At this time, the biochar loaded with Fe3O4 has initially formed a porous structure. 1g of the carbonized product was ball-milled at 300rpm for 2min, and then activated in a carbon dioxide atmosphere. The activation procedure was to increase the temperature to 850℃ at 5℃ / min, maintain for 12h, and the gas flow rate was 100mL / min. After testing, the specific surface area of ​​the activated sample was 1257m 2 / g, total pore volume 0.525cm 3 / g, average pore size 1.67nm. Take 1.0g of the activated product and add 50mL of 10mg / L Cr 6+ The adsorption was carried out at room temperature with 150 rpm shaking for 30 min. 6+ The removal rate was 75%. After separating the adsorbent from the solution with a magnet, the adsorbent was placed in pure water for desorption. After the adsorbent was recovered, the adsorption-desorption process was repeated 5 times. 6+ The removal rate is 67%.

[0032] Example 2

[0033] Take an appropriate amount of bamboo pole crusher and crush it, screen it through 2000 mesh, take the straw under the screen and dry it at 100℃ for 18h. Take 3.0gFeCl3·6H2O and completely dissolve it in 100mL ethylene glycol, then add an appropriate amount of 8.0g NaAc, stir to get a uniform yellow solution, then transfer the solution to a 150mL polytetrafluoroethylene reactor, add 3.0g dry wood powder to the reactor, stir evenly and react at 200℃ for 10h. After cooling to room temperature, centrifuge and wash it with ethanol and deionized water three times, and place it in a 60℃ vacuum drying oven to dry for 6h. Then the product is heated to 150℃ at 5℃ / min in a nitrogen atmosphere, kept for 30min, then heated to 450℃ at 1℃ / min, kept for 2h, and then heated to 700℃ at 5℃ / min, kept for 2h, and then cooled to room temperature naturally. At this time, the biochar loaded with Fe3O4 has initially formed a porous structure. 1g of the carbonized product was ball-milled at 300rpm for 3min, and then activated in a carbon dioxide atmosphere. The activation procedure was to increase the temperature to 870℃ at 5℃ / min, maintain for 12h, and the gas flow rate was 100mL / min. After testing, the specific surface area of ​​the activated sample was 1374m 2 / g, total pore volume 0.553cm 3 / g, average pore size 1.61nm. Take 1.0g of the activated product and add 50mL of 10mg / L Cd 2+ The adsorption was carried out at room temperature with a shaking speed of 150 rpm for 30 min. 2+ The removal rate of Cd was 81%. After separating the adsorbent from the solution with a magnet, the adsorbent was placed in pure water for desorption. After the adsorbent was recovered, the adsorption-desorption process was repeated 5 times. 2+ The removal rate is 73%.

[0034] Example 3

[0035] Take an appropriate amount of nut shells and crush them with a crusher, screen them through 1000 mesh, and take the straw under the screen and dry them at 100℃ for 10h. Take 4.2gFeCl3·6H2O and completely dissolve it in 130mL ethylene glycol, then add an appropriate amount of 11.1g NaAc, stir to get a uniform yellow solution, then transfer the solution to a 200mL polytetrafluoroethylene reactor, add 4.5g of dry straw powder to the reactor, stir evenly and react at 200℃ for 10h. After cooling to room temperature, centrifuge and wash three times with ethanol and deionized water, and place it in a 60℃ vacuum drying oven to dry for 6h. Then the product is heated to 150℃ at 5℃ / min in a nitrogen atmosphere, kept for 30min, then heated to 450℃ at 1℃ / min, kept for 2h, and then heated to 700℃ at 5℃ / min, kept for 2h, and then cooled to room temperature naturally. At this time, the biochar loaded with Fe3O4 has initially formed a porous structure. 1g of the carbonized product was ball-milled at 300rpm for 1min, and then activated in a carbon dioxide atmosphere. The activation procedure was to increase the temperature to 890℃ at 5℃ / min, maintain for 12h, and the gas flow rate was 100mL / min. After testing, the specific surface area of ​​the activated sample was 1699m 2 / g, total pore volume 0.72cm 3 / g, average pore size 1.69nm. Take 1.0g of the activated product and add 50mL of 10mg / L Pb 2+ The adsorption was carried out at room temperature with a shaking speed of 150 rpm for 30 min. 2+ The removal rate was 86%. After separating the adsorbent from the solution with a magnet, the adsorbent was placed in pure water for desorption. After the adsorbent was recovered, the adsorption-desorption process was repeated 5 times. 2+ The removal rate is 78%.

[0036] Example 4

[0037] Take an appropriate amount of corn starch and crush it with a crusher, screen it with 1000 mesh, and take the starch under the screen and dry it at 100℃ for 8h. Take 3.5g FeCl3·6H2O and completely dissolve it in 110mL ethylene glycol, then add an appropriate amount of 11.3g NaAc, stir to get a uniform yellow solution, then transfer the solution to a 150mL polytetrafluoroethylene reactor, add 5.0g dry straw powder to the reactor, stir evenly and react at 200℃ for 10h. After cooling to room temperature, centrifuge and wash it with ethanol and deionized water three times, and place it in a 60℃ vacuum drying oven to dry for 6h. Then the product is heated to 150℃ at 5℃ / min in a nitrogen atmosphere, kept for 30min, then heated to 450℃ at 1℃ / min, kept for 2h, and then heated to 700℃ at 5℃ / min, kept for 2h, and then cooled to room temperature naturally. At this time, the biochar loaded with Fe3O4 has initially formed a porous structure. 2.0 g of the carbonized product was ball-milled at 200 rpm for 1 min, and then activated in a carbon dioxide atmosphere. The activation procedure was to increase the temperature to 900 °C at 5 °C / min, maintain for 12 h, and the gas flow rate was 100 mL / min. After testing, the specific surface area of ​​the activated sample was 1932 m 2 / g, total pore volume 0.818cm 3 / g, average pore size 1.81nm. Take 1.0g of the activated product and add 50mL of 10mg / L Cu 2+ The solution was adsorbed at 150 rpm for 30 min at room temperature. 2+ The removal rate was 92%. After separating the adsorbent from the solution with a magnet, the adsorbent was placed in pure water for desorption. After the adsorbent was recovered, the adsorption-desorption process was repeated 5 times. 2+ The removal rate is 86%.

[0038] The pore structure of the porous carbon material (Table 1) prepared using biochar as the carbon source in the above-mentioned embodiments was detected, and the adsorption performance was verified. The results are shown in Tables 2 and 3.

[0039] Table 1 Distribution ratio of each group in Examples 1-4

[0040]

[0041]

[0042] Table 2 Pore structure parameters of porous carbon materials of Examples 1-4 of the present invention

[0043]

[0044] Table 3 Adsorption properties of porous carbon materials of Examples 1-4 of the present invention

[0045] project Pollutants Initial concentration / mg / L Removal rate / % Removal rate after 5 cycles / % Example 1 <![CDATA[Cr 6+ ]]> 10 75 67 Example 2 <![CDATA[Cd 2+ ]]> 10 81 73 Example 3 <![CDATA[Pb 2+ ]]> 10 86 78 Example 4 <![CDATA[Cu 2+ ]]> 10 92 86

Claims

1. A method for preparing a renewable magnetic porous carbon adsorption material, characterized in that The following processes are used: (1) Preparation of biochar: Select biomass carbon source as raw material, crush and dry to obtain biomass carbon powder, and control the particle size of the biomass carbon powder to be in the range of 2-20 μm; (2) Loading of magnetic material: taking an appropriate amount of FeCl3·6H2O and completely dissolving it in ethylene glycol, then adding an appropriate amount of NaAc, stirring to obtain a uniform yellow solution, then transferring the yellow solution to a polytetrafluoroethylene reactor, adding the biomass carbon powder in step (1) to the reactor, stirring evenly and heating to 180-280°C for high temperature reaction; after the reaction is completed, cooling to room temperature, centrifugally separating and washing with ethanol and deionized water three times, and then drying in a vacuum drying oven; then heating the dried product in a protective atmosphere step by step to a temperature of 600°C-800°C for heat treatment, so that the biomass carbon is carbonized and a biomass carbonized material with a preliminary pore structure is formed; (3) Activation of porous carbon: ball-milling the biomass carbonized material obtained in step (2), and controlling the particle size of the ball-milled product to be in the range of 1-15 μm; activating the ball-milled product in a carbon dioxide atmosphere at a temperature of 800° C.-1000° C. to obtain a magnetic porous carbon adsorption material product.

2. The method for preparing a renewable magnetic porous carbon adsorption material according to claim 1, characterized in that The following steps are also included: S1 parameter test: test the pore structure of the prepared magnetic porous carbon adsorption material, including specific surface area, total pore volume, and average pore diameter; S2 Application effect test: The adsorption performance of the prepared magnetic porous carbon material was tested, including adsorption capacity, adsorption rate, selectivity, recovery rate and cycle performance; S3 Optimization Control: Based on the test results of S1 and S2, the relevant technical parameters of steps (1), (2), and (3) are optimized and controlled to finally produce a product with a specific surface area of ​​>1250m 2 / g, total pore volume>0.52cm 3 / g of magnetic porous carbon adsorption material product.

3. A method for preparing a regenerable magnetic porous carbon adsorption material according to claim 1 or 2, characterized in that: In step (1), the drying procedure is drying at 60-100° C. for 18-24 hours.

4. A method for preparing a regenerable magnetic porous carbon adsorption material according to claim 1 or 2, characterized in that: In step (1), the biomass carbon source includes but is not limited to coconut shells, straws, rice husks, wood, bamboo, bagasse, nut shells, wheat starch, and corn starch; in step (2), the protective atmosphere is nitrogen or argon.

5. A method for preparing a regenerable magnetic porous carbon adsorption material according to claim 1 or 2, characterized in that: In step (2), the mass ratio of FeCl3·6H2O to NaAc is 1:(1.5-4.5), the mass ratio of FeCl3·6H2O to ethylene glycol is 1:(30-40), and the mass ratio of FeCl3·6H2O to biomass carbon source is 1:(1-5).

6. A method for preparing a regenerable magnetic porous carbon adsorption material according to claim 1 or 2, characterized in that: In step (2), the high temperature reaction time is 8-15 hours; the vacuum drying condition is drying at 60-100°C for 6-10 hours; the dried product is heated to 600°C-800°C in a nitrogen protective atmosphere for heat treatment for 1.5-2.5 hours; in step (3), the ball milling condition is processing at a speed of 200-400rpm for 1-5 minutes; the activation temperature is 850°C-950°C, and the activation time is 8-15 hours.

7. The method for preparing a regenerable magnetic porous carbon adsorbent material according to claim 3, characterized in that: In step (1), the biomass carbon source includes but is not limited to coconut shell, straw, rice husk, wood, bamboo, bagasse, nut shell, wheat starch, corn starch; in step (2), the mass ratio of FeCl3·6H2O to NaAc is 1:(1.5-4.5), the mass ratio of FeCl3·6H2O to ethylene glycol is 1:(30-40), and the mass ratio of FeCl3·6H2O to biomass carbon source is 1:(1-5); in step (2), the high temperature reaction time is 8-15h, the vacuum drying condition is drying at 60-100°C for 6-10h, and the dried product is heated to 600°C-800°C in a nitrogen protective atmosphere for heat treatment for 1.5-2.5h; in step (3), the ball milling condition is processing at a speed of 200-400rpm for 1-5min; the activation temperature is 850°C-950°C, and the activation time is 8-15h.

8. The method for preparing a regenerable magnetic porous carbon adsorbent material according to claim 7, characterized in that: In step (2), the mass ratio of FeCl3·6H2O to NaAc is 1:(2.5-3.5), the mass ratio of FeCl3·6H2O to ethylene glycol is 1:(33-39), the mass ratio of FeCl3·6H2O to biomass carbon source is 1:(1-2), the high temperature reaction time is 8-15h, the vacuum drying condition is drying at 60-100°C for 6-10h, and the dried product is heated to 650°C-750°C in a nitrogen protective atmosphere for heat treatment for 1.5-2.5h; in step (3), the ball milling condition is processing at a rotation speed of 200-400rpm for 1-5min, the activation temperature is 850°C-950°C, and the activation time is 8-15h.

9. The method for preparing a regenerable magnetic porous carbon adsorbent material according to claim 8, characterized in that: In step (2), the high temperature reaction temperature is 180-230°C, the high temperature reaction time is 9-12h, the vacuum drying condition is 60-100°C for 6-10h, and the heat treatment time is 1.8-2.5h; in step (3), the activation temperature is 890°C-900°C, and the activation time is 11-13h.

10. The method for preparing a regenerable magnetic porous carbon adsorption material according to claim 9, characterized in that: In step (2), the dried product is heated to 150°C at 5°C / min in a nitrogen atmosphere, maintained for 30 min, then heated to 450°C at 1°C / min, maintained for 2 h, and then heated to 700°C at 5°C / min, maintained for 2 h.

Citation Information

Patent Citations

  • Preparation method of an agricultural biomass carbon-based magnetic adsorbent material

    CN104028214B

  • Preparation method for agriculture biomass carbon-based magnetic adsorption material

    CN104028214A

  • Magnetic biochar adsorbing material and preparation method thereof

    CN106362690A

  • Preparation method and application of general magnetic adsorbent

    CN108393073A

  • Method for preparing carbon-based magnetic activated carbon and prepared carbon-based magnetic activated carbon

    CN114392719A